China’s dual-goal society: Evaluation method and empirics - Jia, R.; Zhao, D.; Guo, X.; Marinova, Dora (The Modelling and Simulation Society of Australia and New Zealand Inc, 2011)
In 2005 China announced that together with further economic development, resource efficiency and protection of the natural environment are becoming policy objectives. This is referred to as a dual-goal society and the study examines China’s progress in achieving these objectives. It puts forward a model to assess China’s performance from the point of view of resource efficiency and environmental friendliness. This model is then applied to analyse data from 30 provinces over the 2003-2009 period. The analysis shows that China’s fast developing dual-goal society has created a serious regional imbalance. These disparities need to be adjusted for the dual goal to be achieved at a country level. Further challenges associated with the factors influencing the development of a dual-goal society and how they impact on China’s national policies and strategies are also discussed.